Genome-Wide Identification and Analysis of Glycosyltransferases in Colletotrichum graminicola - Yafei Wang; Honglian Li; Jiaxin Chang; Yu Zhang; Jinyao Li; Shaofeng Jia; Yan Shi (Microorganisms)
Corn leaf blight and stem rot caused by Colletotrichum graminicola are significant diseases that severely affect corn crops. Glycosyltransferases (GTs) catalyze the transfer of sugar residues to diverse receptor molecules, participating in numerous biological processes and facilitating functions ranging from structural support to signal transduction. This study identified 101 GT genes through functional annotation of the C. graminicola TZ–3 genome. Subsequent analyses revealed differences among the C. graminicola GT (CgGT) genes. Investigation into subcellular localization indicated diverse locations of CgGTs within subcellular structures, while the presence of multiple domains in CgGTs suggests their involvement in diverse fungal biological processes through versatile functions. The promoter regions of CgGT genes are enriched with diverse cis-acting regulatory elements linked to responses to biotic and abiotic stresses, suggesting a key involvement of CgGT genes in the organism’s multi-faceted stress responses. Expression pattern analysis reveals that most CgGT genes were differentially expressed during the interaction between C. graminicola and corn. Integrating gene ontology functional analysis revealed that CgGTs play important roles in the interaction between C. graminicola and corn. Our research contributes to understanding the functions of CgGT genes and investigating their involvement in fungal pathogenesis. At the same time, our research has laid a solid foundation for the development of sustainable agriculture and the utilization of GT genes to develop stress-resistant and high-yield crop varieties.